Anion exchange membrane with supramolecular responsive channel as well as preparation method and application of anion exchange membrane
By introducing porphyrin and crown ether structures into the anion exchange membrane, supramolecular responsive channels are constructed, which solves the problems of easy degradation and low conductivity of traditional membranes in alkaline environments, achieving higher chemical stability and ion selectivity, and significantly reducing resistance.
Patent Information
- Application Number
- CN202510040257.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Traditional anion exchange membranes are prone to degradation in alkaline environments, have low conductivity, poor ion selectivity, and have reduced efficiency in complex ion environments, limiting their reliability and service life under strong alkaline conditions.
Anion exchange membrane with supramolecular responsive channels is adopted to improve the chemical stability and ion transmittance of the membrane and reduce the resistance by introducing porphyrin and crown ether structures.
The chemical stability and pH response ability under different acid and alkali conditions are achieved, which significantly reduces the resistance of the membrane, improves ion selectivity and transmittance, and extends the service life.
Smart Images

Figure BDA0005236720970000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrodialysis, and in particular relates to an anion exchange membrane with a supramolecular responsive channel and a preparation method and application thereof. Background Art
[0002] In the process of anion exchange membrane material development, although traditional membrane materials have been applied in many fields, they have gradually exposed several shortcomings. Generally, these membranes rely on classic ion exchange groups such as quaternary ammonium salts and tertiary amine groups. However, this design faces many challenges in use.
[0003] First, quaternary ammonium salt-structured anion exchange membranes are prone to Hofmann degradation in alkaline environments, resulting in reduced chemical stability and material inactivation, which weakens their reliability and service life under strong alkaline conditions. Although tertiary amine-type ion exchange membranes have improved their alkali resistance by introducing tertiary amine groups, the resulting conductivity problem limits their widespread application. In addition, due to their relatively simple structure, traditional membranes are not well adapted to complex ionic environments, resulting in poor ion selectivity, especially when multi-component ions coexist, the efficiency of the membrane is greatly reduced.
[0004] Secondly, due to the limitations of the ion channel design in traditional anion exchange membranes, their ion permeability is poor, affecting the processing speed and efficiency. This problem is particularly evident in rapid processing requirements and large-scale industrial applications, becoming a bottleneck restricting its application. The traditional membrane structure lacks flexibility and adaptability, resulting in low ion transmission efficiency and increased resistance in practical applications. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an anion exchange membrane with supramolecular responsive channels and a preparation method and application thereof. The anion exchange membrane prepared by the present invention has low resistance, visualized pH response and good desalination performance, and can be used in the field of electrodialysis desalination membrane material technology.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is:
[0007] In a first aspect, an embodiment of the present invention provides a method for preparing an anion exchange membrane having a supramolecular responsive channel, comprising the following steps:
[0008] (1) Take 3-5 g of biphenyl, 0.5-1 g of dibenzo-18-crown-6, 4-5 mL of N-methyl-4-piperidone and 0.01-0.2 g of tetraphenylporphyrin, and dissolve the above substances in 5-20 mL of dichloromethane;
[0009] (2) under ice bath conditions, 1 to 3 mL of trifluoroacetic acid is added dropwise to the mixed solution in step (1) at a constant rate, and then 10 to 33 mL of trifluoromethanesulfonic acid is added, and the reaction is continued for 3 to 5 hours;
[0010] (3) pouring the green viscous mixture into deionized water to elute to obtain a solid;
[0011] (4) taking 0.5-1 g of the solid obtained in step (3) and dissolving it in 10-15 mL of a casting solvent to obtain a green transparent solution;
[0012] (5) Pour the above transparent solution onto a glass plate, place it in a vacuum drying oven, and dry it at 60-80° C. for 10-24 h to obtain an anion exchange membrane.
[0013] Furthermore, in step (4), the film casting solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide.
[0014] Furthermore, in step (5), the thickness of the anion exchange membrane is controlled to be 80 to 110 μm.
[0015] Furthermore, in step (3), when eluting with deionized water, elution is performed 3 to 5 times to ensure that the residual solvent is completely eluted.
[0016] Furthermore, the anion exchange membrane is soaked in an acidic aqueous solution before use.
[0017] In a second aspect, an embodiment of the present invention provides an anion exchange membrane having supramolecular responsive channels, which is prepared by the preparation method described in the first aspect.
[0018] In a third aspect, an embodiment of the present invention provides an application of the anion exchange membrane with supramolecular responsive channels described in the second aspect as a membrane material for electrodialysis desalination.
[0019] The technical solution provided by the embodiment of the present invention has the following beneficial effects:
[0020] 1) Enhanced chemical stability: The present invention adopts a porphyrin structure to make the membrane show color changes under different acid and alkaline conditions, providing intuitive pH response capabilities. This visual feature helps monitor the usage status while also improving the chemical stability of the membrane and extending its service life, making it more reliable than traditional membranes.
[0021] 2) Lower resistance: The optimized design of the supramolecular structure enables the new anion exchange membrane to effectively reduce the resistance of the membrane, especially in synergy with the tertiary amine structure, which significantly improves the conductivity, which is crucial for efficient desalination process.
[0022] 3) Easy to industrialize: The preparation process of the anion exchange membrane with supramolecular responsive channels of the present invention is simple, and no quaternization is required. The synthesis steps are simple and easy to industrialize. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] Example 1
[0025] A method for preparing an anion exchange membrane having a supramolecular responsive channel comprises the following steps:
[0026] (1) Take 4.2 g of biphenyl, 0.9 g of dibenzo-18-crown-6, 4.1 mL of N-methyl-4-piperidone and 0.02 g of tetraphenylporphyrin and dissolve them in 10 mL of dichloromethane;
[0027] (2) under ice bath conditions, 2 mL of trifluoroacetic acid was added dropwise to the mixed solution in step (1) at a constant rate, and then 25 mL of trifluoromethanesulfonic acid was added, and the reaction was continued for 4 hours;
[0028] (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a colored solid (the green color will become darker as the amount of tetraphenylporphyrin increases);
[0029] (4) 0.75 g of the solid polymer obtained in step (3) was dissolved in 15 mL of dimethyl sulfoxide to obtain a green transparent solution;
[0030] (5) The green transparent solution was poured onto a glass plate, placed in a vacuum drying oven, and dried at 80° C. for 24 h to obtain a weakly alkaline anion exchange membrane AEM-1.
[0031] Example 2
[0032] A method for preparing an anion exchange membrane having supramolecular responsive channels comprises the following steps:
[0033] (1) Take 4.2 g of biphenyl, 0.9 g of dibenzo-18-crown-6, 4.1 mL of N-methyl-4-piperidone and 0.04 g of tetraphenylporphyrin and dissolve them in 10 mL of dichloromethane;
[0034] (2) under ice bath conditions, 2 mL of trifluoroacetic acid was added dropwise to the mixed solution in step (1) at a constant rate, and then 25 mL of trifluoromethanesulfonic acid was added, and the reaction was continued for 4 hours;
[0035] (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a colored solid (the green color will become darker as the amount of tetraphenylporphyrin increases);
[0036] (4) 0.75 g of the solid polymer obtained in step (3) was dissolved in 15 mL of dimethyl sulfoxide to obtain a green transparent solution;
[0037] (5) The green transparent solution was poured onto a glass plate, placed in a vacuum drying oven, and dried at 80° C. for 24 h to obtain a weakly alkaline anion exchange membrane AEM-2.
[0038] Example 3
[0039] A method for preparing an anion exchange membrane having supramolecular responsive channels comprises the following steps:
[0040] (1) Take 4.2 g of biphenyl, 0.9 g of dibenzo-18-crown-6, 4.1 mL of N-methyl-4-piperidone and 0.1 g of tetraphenylporphyrin and dissolve them in 10 mL of dichloromethane;
[0041] (2) under ice bath conditions, 2 mL of trifluoroacetic acid was added dropwise to the mixed solution in step (1) at a constant rate, and then 25 mL of trifluoromethanesulfonic acid was added, and the reaction was continued for 4 hours;
[0042] (3) pouring the green viscous mixture obtained in step (2) into deionized water for elution to obtain a colored solid (the green color will become darker as the amount of tetraphenylporphyrin increases);
[0043] (4) 0.75 g of the solid polymer obtained in step (3) was dissolved in 15 mL of dimethyl sulfoxide to obtain a green transparent solution;
[0044] (5) The green transparent solution was poured onto a glass plate, placed in a vacuum drying oven, and dried at 80° C. for 24 h to obtain a weakly alkaline anion exchange membrane AEM-3.
[0045] The performance of the anion exchange membranes prepared in Examples 1-3 was tested below:
[0046] Test 1: The anion exchange membranes prepared in Examples 1-3 were subjected to resistance tests and compared with commercial quaternary ammonium type AMX and tertiary amine type ACM anion exchange membranes.
[0047] Table 1 Comparison of membrane surface resistance of anion exchange membranes prepared in Examples 1-3 and commercial membranes with different functional groups
[0048]
[0049] As can be seen from Table 1, the tertiary amine anion exchange membrane prepared in Examples 1-3 exhibits lower resistance under direct test conditions due to its unique structure, which is particularly prominent compared to the traditional tertiary amine anion exchange membrane ACM. After activation by an acidic solution, the membrane surface resistance of the tertiary amine anion exchange membrane prepared in Examples 1-3 is comparable to that of the commercial membrane quaternary ammonium AMX. This shows that the tertiary amine anion exchange membrane can efficiently respond to pH changes and significantly reduce energy consumption.
[0050] Test 2: The chemical stability of the anion exchange membranes prepared in Examples 1-3 in sodium hydroxide solution was tested to investigate the chemical stability of the anion exchange membranes. The chemical stability was evaluated using the weight loss rate as an indicator and the weight difference as an indicator. The results are shown in Table 2.
[0051] When conducting a weight loss test, the following steps are included:
[0052] (1) After the weakly alkaline anion exchange membrane prepared in Examples 1-3 and the commercial membrane quaternary ammonium AMX were completely dried in a vacuum oven at 80° C. for 24 h, the weight of the sample was recorded;
[0053] (2) Soak the dried ion exchange membrane sample in a 2.0 M sodium hydroxide solution at 80°C for 24 h, 48 h, and 96 h, then carefully wipe the retained solution on the surface of the sample and wash the soaked membrane with water until the water becomes neutral;
[0054] (3) The ion exchange membrane samples were dried at 80 °C under vacuum conditions for 24 h, and then the membrane weight was re-weighed. The weight loss was used to characterize the alkali stability of the membrane.
[0055] Table 2 Weight loss rate of membranes immersed in 2.0 mol / L sodium hydroxide solution at different time periods
[0056] Time (h) 24 48 96 AMX weight loss rate (%) 10.2 15.2 19.3 AEM-1 weight loss rate (%) 1.2 1.5 1.6 AEM-2 weight loss rate (%) 1.3 1.5 1.6 AEM-3 weight loss rate (%) 1.1 1.2 1.3
[0057] As can be seen from Table 2, the conventional quaternary ammonium anion exchange membrane AMX often loses weight to a certain extent due to Hofmann degradation. However, the tertiary amine anion exchange membrane prepared in Examples 1-3 exhibits a lower weight loss rate due to its unique stability structure and the characteristics of the tertiary amine functional group, further highlighting its superior chemical stability.
[0058] Test 3: The water absorption rate of the anion exchange membrane prepared in Examples 1-3 was compared with that of the commercial membrane quaternary ammonium type AMX at different temperatures. The specific operation is as follows: After the tested membrane sample is completely dried in a vacuum drying oven at 80°C for 24 hours, the length of the membrane sample is recorded, and then the dried ion exchange membrane sample is soaked at 20°C, 30°C, and 40°C for 48 hours, and the retained solution on the surface of the sample is carefully wiped, the weight of the membrane sample is recorded, and the weight change of the sample compared to the dry state is calculated.
[0059] Table 3 Water absorption of anion exchange membrane and AMX membrane prepared in Examples 1-3 at different temperatures
[0060] Sample No. 20℃(%) 30℃(%) 40℃(%) AMX 20.21 25.88 31.79 AEM-1 10.05 12.58 14.38 AEM-2 12.15 13.78 15.13 AEM-3 15.87 16.23 17.33
[0061] As can be seen from Table 3, the anion exchange membranes prepared in Examples 1-3 have a rigid polymer skeleton, and their water absorption rate changes when the temperature rises are far less significant than that of the AMX membrane with a flexible polymer chain structure. This shows that the anion exchange membranes prepared in Examples 1-3 have good thermal stability and are not easily deformed by heat, thus showing excellent structural stability in a high temperature environment.
[0062] The present invention introduces porphyrin and crown ether supramolecular structures and provides an anion exchange membrane with supramolecular responsive channels. The porphyrin structure gives the membrane pH response characteristics, so that it presents different colors under different acid and alkaline conditions. This visualization characteristic not only improves the state monitoring capability of the membrane, but also provides users with intuitive operation guidance. The supramolecular channel formed by the crown ether structure effectively increases the ion cross-chain transport capacity of the membrane, improves the ion permeability, and significantly reduces the resistance, especially when it works together with the tertiary amine structure, it shows more obvious advantages.
[0063] By integrating these innovative supramolecular designs, the anion exchange membrane produced by the present invention is able to comprehensively surpass traditional membranes in performance. It not only has higher chemical stability and ion selectivity, but also excels in transmittance and resistance optimization. Such progress fully demonstrates that the application of supramolecular chemistry in membrane material science has great potential, and provides a solid foundation and broad prospects for future technological development and practical applications.
[0064] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an anion exchange membrane having a supramolecular responsive channel, characterized in that: The steps include: (1) Take 3-5 g of biphenyl, 0.5-1 g of dibenzo-18-crown-6, 4-5 mL of N-methyl-4-piperidone and 0.01-0.2 g of tetraphenylporphyrin, and dissolve the above substances in 5-20 mL of dichloromethane; (2) In an ice bath, add 1-3 mL of trifluoroacetic acid to the mixed solution in step (1) at a constant rate, and then add 10-33 mL of trifluoromethanesulfonic acid, and continue the reaction for 3-5 hours; (3) Pour the green viscous mixture into deionized water to elute to obtain a solid; (4) Take 0.5-1 g of the solid obtained in step (3) and dissolve it in 10-15 mL of a casting solvent to obtain a green transparent solution; (5) Pour the above transparent solution onto a glass plate, place it in a vacuum drying oven, and dry it at 60-80°C for 10-24 hours to obtain an anion exchange membrane.
2. The method for preparing an anion exchange membrane having supramolecular responsive channels according to claim 1, characterized in that: In step (4), the film casting solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide.
3. The method for preparing an anion exchange membrane having supramolecular responsive channels according to claim 1, characterized in that: In step (5), the thickness of the anion exchange membrane is controlled to be 80-110 μm.
4. The method for preparing an anion exchange membrane having supramolecular responsive channels according to claim 1, characterized in that: In step (3), when eluting with deionized water, elute 3 to 5 times to ensure that the residual solvent is completely washed away.
5. The method for preparing an anion exchange membrane having supramolecular responsive channels according to claim 1, characterized in that: The anion exchange membrane is soaked in an acidic aqueous solution before use.
6. An anion exchange membrane having supramolecular responsive channels, prepared by the preparation method according to any one of claims 1 to 5.
7. The use of an anion exchange membrane having supramolecular responsive channels according to claim 6, characterized in that: As membrane material for electrodialysis desalination.
Citation Information
Patent Citations
Preparation method of porphyrin / nano porous fiber membrane hydrogen chloride gas sensor
CN106442497A
Branched poly (aryl piperidinium) anion exchange membrane as well as preparation method and application thereof
CN115678073A
Hyperbranched anion exchange membrane as well as preparation method and application thereof
CN116731366A
Anion exchange membrane and method for producing same
CN116801967A